Understanding Fathers’ Loneliness in Relation to Psychological and Social Factors - Ersa Lanang Sanjaya; Prisca Eunike (Universitas PGRI Yogyakarta, 2026)
Loneliness in fathers is a relevant psychological issue but remains understudied. Most research on loneliness focuses on the elderly, mothers, or adolescents, while fathers are often overlooked. However, changes in roles after becoming a father may also place men at risk of loneliness. This study examines paternal loneliness from the perspectives of parenting self-efficacy, job stress, marital satisfaction, and sense of community, with meaning in life as a moderator. A quantitative research design with a PLS-SEM approach was used. The participants were 256 married fathers who lived with their spouses and had children no older than 5 years. Data were collected using self-report questionnaires in a cross-sectional design. The results revealed that meaning in life moderated the effects of parenting self-efficacy and sense of community on loneliness, but not the effect of job stress. Job stress had a direct impact on loneliness, while marital satisfaction showed no significant relationship with either meaning in life or loneliness. These findings highlight meaning in life as a protective factor against loneliness in fathers. Keywords: fathers’ loneliness, meaning in life, parental self-efficacy, job stress, sense of community, Indonesia